2022
DOI: 10.3389/fmicb.2022.1048997
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, accurate, and novel diagnostic technique for respiratory pathogens: Clinical application of loop-mediated isothermal amplification assay in older patients with pneumonia, a multicenter prospective observational study

Abstract: BackgroundLoop-mediated isothermal amplification (LAMP) is a novel nucleic acid amplification method using only one type of enzyme that can amplify DNA with high specificity, efficiency and rapidity under isothermal conditions. Chips for Complicated Infection Detection (CCID) is based on LAMP. This study translate CCID into clinical application and evaluate its diagnostic value for pneumonia.MethodsEighty one older patients with pneumonia were prospectively enrolled from January 1 to July 23, 2021, and 57 sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The chip was able to identify 47 bacterial species, 22 fungal species and 21 viruses. 12 The workflow of mNGS includes sample pretreatment and nucleic acid extraction, library preparation, highthroughput sequencing, and bioinformatics analysis. Nucleic acid extraction and library preparation were performed.…”
Section: Sample Collection and Pathogen Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chip was able to identify 47 bacterial species, 22 fungal species and 21 viruses. 12 The workflow of mNGS includes sample pretreatment and nucleic acid extraction, library preparation, highthroughput sequencing, and bioinformatics analysis. Nucleic acid extraction and library preparation were performed.…”
Section: Sample Collection and Pathogen Detectionmentioning
confidence: 99%
“…Chips for complicated infection detection (CCID) is a novel technique for rapid detection of pathogenic microorganisms. 12 Our previous multicenter prospective observational study has shown that CCID was promising in elderly patients with pneumonia due to its potential to rapidly and accurately detect multiple pathogenic microorganisms and was less affected by prior antimicrobial therapy. 12 In addition, metagenomic next-generation sequencing (mNGS), as a hypothesis-free, unbiased, and culture-independent modality, has been progressively applied in the etiological diagnosis of respiratory tract infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation